AN ANALYSIS ON FIGURATIVE LANGUAGE USED IN EBIT G. ADE’S SONGS IN „BEST OF THE BEST‟ ALBUM - SUSANTI, GLADYS DAMEFRIZA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Song, lyric, figurative language, semantics, and Ebit G. AdeSong is a poem, which is sounded. It is also defined as a combination between musicand word. Song is not only used to convey a life story, but it is also an amusement for the listeners. To make a song became more artistic the composer often used figurative language to express their work. Therefore, the writer analyzed the use of figurative language and its sustainabilit y wit h contextual meaning in Ebit G. Ade songs in “Best of the Best” album. There were two problems to be solved in this analysis, namely (1) what are the kinds of figurative language found in the lyrics of Ebit G. Ade‟s songs in “Best of the best” album; (2) what is the contextual meaning of the figurative language related to the lyrics. Based on the problems that were formulated, there were two objectives of the study, those are (1) to find out the kinds of figurative language which are used in the lyrics of Ebit G. Ade‟s songs in “Best of The Best” album; (2) to understand the contextual meaning of the figurative language related to the lyrics.In this analysis, the theory was taken from Keraf to find the kinds of figurative language used in all of song lyrics of Ebit G. Ade in “Best of the Best” album. Furthermore, the theory of semantics from Saeed were used to interpret the contextual meaning found in Ebit G. Ade song lyrics.This analysis used descriptive qualitative approach. Based on the problems of the study, this analysis discussed the phenomenon of kinds of figurative language and its contextual meaning of Ebit G. Ade‟s song lyrics. The data is taken from the whole song lyrics of his thirteenth album, entit led „Best of the best‟. This album contains of fifteen best collect ion of Ebit G. Ade‟s songs.After finishing the analysis, the result showed that there were eighteen kinds offigurative language used in Ebit G. Ade‟s songs. The use of repetit ion is mostly found in each of his songs, followed by climax, personification, hyperbole, irony, and others. Furthermore, it is also discovered the contextual meaning of figurative language which was used in each song lyrics.At the end of the analysis, the writer conclude that every song of Ebit G. Ade haddifferent kind of figurative language. Furthermore, each of figurative language used in Ebit G. Ade‟s songs had meaning that could be analyzed contextually. The writer suggested for the next researchers to research other song lyrics of Ebit G. Ade or other singers, with the same data but investigated from different point of view.